THE TUNJUNGAN STREET’S PHYSICAL EVIDENCE THAT ATTRACT THE VISITOR IN SURABAYA - Sutikno, Keisha Amabel Saputra; Irwanto, Billy Jovian; Sebastian, Immanuel; Soewitno, Vanessa Eileen; Harsono, Yovita Aryani; Mahendra, Rico; Kusumowidagdo, Astrid (Universitas Ciputra Surabaya, 2024)
One of the iconic tourist attractions in Surabaya City is Tunjungan Street, which recently has regained public attention. After the government declared it to be “asleep” in 1990, this tourism was finally attempted to return by the Surabaya government. Moreover, the improvement in the economic sector, mainly in the MSMEs sector, has also become one of the reasons why Tunjungan Street started to be intensively developed again by the Surabaya government. The interesting thing about this area is that the researchers obtained opportunities to define physical evidence of the area, which is a marketing tactic and also evidence of the existence of a sense of place in this area. The aim of this research is to understand the reason for the government’s success in reviving Tunjungan Street. This research used a qualitative method using a case study, supported by going directly to Tunjungan Street to observe the surrounding conditions. The results of the research revealed that physical evidence has proven to contribute to the marketing of the Tunjungan area. The results showed that the Tunjungan area, architecture, interior, and focal point became attractive physical evidence. This is shown by the crowding, interactions between visitors and sellers, and the friendly atmosphere along the corridor of Tunjungan Street. This research can be used for future consideration in forming a public space in a historical area. Keywords: Architecture, Marketing Mix, Physical Evidence, Sense of Place, Tunjungan Street.